Till mortgage do us part: Mortgage switching costs and household's bank switching - Brunetti, M.; Ciciretti, R.; Djordjevic, Lj. (Journal of Banking & Finance, 2020)
We investigate the role of mortgage switching costs in shaping the households’ decision to change their main bank. To this end, we use a unique panel dataset that enables us to infer household's bank switching, in conjunction with a legal reform that exogenously slashed down the mortgage switching costs. The empirical evidence, which survives to a variety of robustness checks, supports the hypothesis that the explicit switching costs in the retail banking market are a weighty factor in shaping households’ bank switching, despite any potential “informational lock-in”. Dissecting the results, we show that the effects of the reform were not uniform across households. The more educated households, those with a longer or broader relationship with their previous bank and those residing in ex-ante less competitive banking markets were at the forefront of the wave of bank switching.